'Bare-bones' to 'silver linings': lessons on integrating a palliative approach to care in long-term care in Western Canada - Denise Cloutier; Kelli I. Stajduhar; Della Roberts; Carren Dujela; Kaitlyn Roland (BMC, 2021)
Abstract Background 'Whole-person' palliative approaches to care (PAC) are important for enhancing the quality of life of residents with life-limiting conditions in long-term care (LTC). This research is part of a larger, four province study, the 'SALTY (Seniors Adding Life to Years)' project to address quality of care in later life. A Quality Improvement (QI) project to integrate a PAC (PAC-QI) in LTC was implemented in Western Canada in four diverse facilities that varied in terms of ownership, leadership models, bed size and geography. Two palliative 'link nurses' were hired for 1 day a week at each site over a two-year time frame to facilitate a PAC and support education and training. This paper evaluates the challenges with embedding the PAC-QI into LTC, from the perspectives of the direct care, or front-line team members. Sixteen focus groups were undertaken with 80 front-line workers who were predominantly RNs/LPNs (n = 25), or Health Care Aides (HCAs; n = 32). A total of 23 other individuals from the ranks of dieticians, social workers, recreation and rehabilitation therapists and activity coordinators also participated. Each focus group was taped and transcribed and thematically analyzed by research team members to develop and consolidate the findings related to challenges with embedding the PAC. Results Thematic analyses revealed that front-line workers are deeply committed to providing high quality PAC, but face challenges related to longstanding conditions in LTC notably, staff shortages, and perceived lack of time for providing compassionate care. The environment is also characterized by diverse views on what a PAC is, and when it should be applied. Our research suggests that integrated, holistic and sustainable PAC depends upon access to adequate resources for education, training for front-line care workers, and supportive leadership. Conclusions The urgent need for integrated PAC models in LTC has been accentuated by the current COVID-19 pandemic. Consequently, it is more imperative than ever before to move forwards with such models in order to promote quality of care and quality of life for residents and families, and to support job satisfaction for essential care workers.